2006
DOI: 10.1088/0954-3899/34/1/009
|View full text |Cite
|
Sign up to set email alerts
|

Search for new particles decaying into electron pairs of mass below 100 MeV/c2

Abstract: We report results on 1220 electron pairs produced from a 207Pb beam at 160 A GeV in nuclear emulsion with invariant mass Q ranging between 1 and 100 MeV and lifetime τ between 10−15 s and 10−12 s. These electron pairs were produced at a distance of more than 50 µm from the primary interactions—this distance eliminates contamination due to Dalitz pairs. After subtracting the background pairs from the materialization of photons and also due to the decay of π0 → 2γ from the data, they exhibit enhancement at low m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 30 publications
3
36
1
Order By: Relevance
“…Supporting evidence for this hypothetical X17 particle has been reported recently in the decay of the excited I(J π ) = 0(0 − ) state of 4 He [16]. Earlier observations of similar e + e − pairs with invariant masses between 3 to 20 MeV in the collision of nuclei with emulsion detectors have been reported [17][18][19][20][21][22]. Different theoretical interpretations, astrophysical implications, and experimental searches have been presented [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 76%
“…Supporting evidence for this hypothetical X17 particle has been reported recently in the decay of the excited I(J π ) = 0(0 − ) state of 4 He [16]. Earlier observations of similar e + e − pairs with invariant masses between 3 to 20 MeV in the collision of nuclei with emulsion detectors have been reported [17][18][19][20][21][22]. Different theoretical interpretations, astrophysical implications, and experimental searches have been presented [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 76%
“…An important problem is determining nature of dark Universe. It is found that the dark matter may be consists of neutrinos [1] axions [2] or WIMPs (weak interactive massive particles) [3]. In that case there are several ways to specify the nature of the dark Universe.…”
Section: Introductionmentioning
confidence: 99%
“…of the electron, might also reveal itself at low energies through synchronisation between the constituents of the composite electrons in ferromagnetic electron liquids [179] and lowdimensional electron systems, like Wigner crystals [180]. Another possibility is to detect some exotic electron bound states, like those observed by Jain and Singh [181] in their experiments at CERN aimed at searching for low-mass neutral particles decaying into e + e − pairs. They have reported the detection of short-lived neutral particles having masses of 7 ± 1 MeV and 19 ± 1 MeV.…”
Section: A Hierarchy Of Preonic Bound Statesmentioning
confidence: 97%